Current Developments in 3D Bioprinting for Tissue and Organ Regeneration–A Review - Agarwal, Swarnima; Saha, Shreya; Balla, Vamsi Krishna; Pal, Aniruddha; Barui, Ananya; Bodhak, Subhadip (Frontiers in Mechanical Engineering, 2020)
The field of Tissue engineering and regenerative medicine that work towards creating functional tissue-constructs mimicking native tissue for repair and/or replacement of damaged tissues or whole organs have evolved rapidly over the past few decades. However, traditional tissue engineering approaches comprising of scaffolds, growth factors and cells showed limited success in fabrication of complex 3D shapes and in vivo organ regeneration leading to their non-feasibility for clinical applications from a logistical and economical viewpoint. In this regard, 3D bioprinting, which is an extended application of additive manufacturing is now being explored for tissue engineering and regenerative medicine as it involves the top-down approach of building the complex tissue in a layer by layer fashion, thereby producing precise geometries due to controlled nature of matter deposition with the help of anatomically accurate 3D models of the tissue generated by computer graphics. Here, we aim to provide a comprehensive review of the 3D bioprinting technology along with associated 3D bioprinting strategies including ink-jet printing, extrusion printing, stereolithography and laser assisted bioprinting techniques. We then focus on the applications of 3D bioprinting technology on construction of various representative tissue and oragans, including skin, cardiac, bone and cartilage etc. We further attempt to highlight the steps involved in each of those tissues/organs printing and discuss on the associated technological requirements based on the available reports from recent literature. We finally conclude with current challenges with 3D bioprinting technology along with potential solution for future technological advancement of efficient and cost-effective 3D bioprinting methods.